Contextualisation of Zakat in the Qur'an From the Perspective of Kuntowijoyo Islamic Epistemology - Rufi'ah Rufi'ah (ADP Publisher, 2025)
Natural disasters and epidemics are major humanitarian challenges, necessitating the help of others to resolve them. One way to do this is through the distribution of zakat. Zakat is a form of philanthropy with the potential to channel humanitarian funds. However, because zakat has been defined by the categories of recipients mentioned in the Qur'an, while the victims who need assistance vary widely, it is necessary to re-examine the concept of zakat recipients so that its objectives can be achieved. In an effort to reinterpret the concept of zakat recipients, this paper will utilize Kuntowijoyo's Islamic scholarly approach, namely moving from text to context. Based on the demystification (contextualization) of zakat in the Qur'an, the epistemological perspective of Islamic scholarship illustrates that subjectively, zakat aims not only to purify the soul and wealth of the zakat payer as a form of devotion to God. More broadly, zakat aims to eliminate poverty, alleviate the suffering of victims of natural disasters (COVID-19), and create prosperity and social justice. Thus, based on the Islamic scientific project, zakat as an Islamic teaching with various benefits and implications can be accepted by anyone, even other religions, without being forced as a teaching, but as knowledge. This is also in line with the principles and mission of Islamic philanthropy.